Pre-weaning performance and growth curve in F1 Katahdin x East Friesian crossbred lambs - Salinas-González, H.; Maldonado-Jáquez, J. A.; Baughman, C.; Zadok, A. O.; Torres-Hernández, G.; Montelongo-Gutiérrez, Z. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
The aim was to evaluate the pre-weaning performance of F1 Katahdin × East Friesian (Kt x EF) crossbred lambs, focused on growth and weaning weight. A total of 43 lambs with their dams were raised on pasture. Litter size and progeny sex were considered. Five nonlinear models were used to describe the growth curve. A significant interaction effect (P< 0.05) was found for sex and group effect for litter size on daily weight gain and weaning weight, with males and lambs from triplet and single births achieving the highest weight gains. No interaction effects or group differences were observed for birth weight, weaning age, or mortality (P> 0.05) due to progeny sex or litter size. Positive and signifi-cant correlations were observed. The Von Bertalanffy and Richards models showed the best fit for the growth curve, with R² values exceeding 98%. In conclusion, under grazing conditions, F1 Kt × EF lambs showed similar birth weights and higher weaning weights in those born as singles or triplets, suggesting a strong heterosis effect. Furthermore, the Von Bertalanffy and Richards models provided the best fit to describe the growth curve.